Classical Hodgkin Lymphoma as a Second Malignancy in a Patient With Cervical Squamous Cell Carcinoma Following Chemoradiotherapy: A Case Report - Xin, Zhemei; Wang, Chengshi (AME Case Reports, 2026)
Background: Concurrent chemoradiotherapy is the established standard treatment for locally advanced cervical cancer. However, it may increase the risk of second primary malignancies in long-term survivors.Case Description: This report describes a case of classical Hodgkin lymphoma (cHL) arising as a secondary neoplasm in a patient with cervical squamous cell carcinoma who was treated with definitive chemoradiotherapy. The patient was a 65-year-old woman diagnosed with stage ⅢB cervical squamous cell carcinoma in 2020. She received three cycles of cisplatin-based chemotherapy combined with image-guided radiation therapy (IGRT). In August 2025, she presented with persistent fever, productive cough and systemic lymphadenopathy. Initial investigations confirmed severe acute respiratory syndrome corona-virus 2 (SARS-CoV-2) infection and extensive lymph node enlargement on cross-sectional imaging. Despite clinical resolution of the SARS-CoV-2 infection and empirical antibiotic therapy, she continued to experience recurrent high-grade fever. Excisional biopsy of an intact enlarged right axillary lymph node was performed and pathological examination confirmed cHL. After Positron Emission Tomography/Computed Tomography (PET/CT) examination, she was diagnosed as stage IVB cHL. After four cylces of tislelizumab combined with the AVD regimen consisting of pirarubicin, vinblastine and dacarbazine, the patient achieved complete resolution of symptoms.Conclusions: Radiotherapy, cisplatin-based chemotherapy, Epstein-Barr virus (EBV) activation, age-related immunosenescence, poorly controlled long-term diabetes mellitus (DM) and SARS-CoV-2 infection-related immunosuppression may have collectively contributed to lymphomagenesis. This case highlights the critical need for sustained long-term follow-up in cervical cancer patients, especially those burdened with concurrent chronic diseases. In the setting of unexplained fever or lymphadeno-pathy, clinicians must differentiate secondary malignancies from primary tumor recurrence. During the pathological diagnostic process, examination an intact lymph node is essential for diagnosis.